Asymmetrical power relations: a legal analysis of the European Union and Economic Community of West African States Economic Partnership Agreement - Agbo-Ejeh, Christiana I (Department of Commercial Law, 2023)
Preparatory to the Economic Partnership Agreements (EPAs) negotiation, the former European Union Trade Commissioner, Peter Mandelson, declares that African countries have the right to benefit from their own comparative advantage. He further stated that the EPAs would, inevitably, herald the end of the colonial ideological construct of the previous trading system and usher in mutually beneficial economic development. However, as negotiated between the EU and ECOWAS, the EPA reflects a ‘systemic' asymmetry originating in colonialism to a certain extent. This thesis argued that just as the GATT advanced a structure of trade liberalisation and trade laws that perpetuate asymmetry in favour of the developed countries, the EU-African Caribbean and Pacific (ACP) countries EPAs, which promote free trade, are likely to continue the asymmetry between the EU-ACP countries and the EU-ECOWAS in particular. In order to gather in-depth insights into the EU-ECOWAS Economic Partnership Agreement, empirical evidence was used to triangulate between primary and secondary sources, mainly in chapters five to seven of this thesis for analysis. This method involved interviews in ECOWA with Commission, Ministries in Ghana, Nigeria and archival documents obtained from organisations. The approach offers an effective means to gain insights into the real issues canvassed by the opponents of the EPA and the current impasse in the trade relationship between the two regions. Ghana and Nigeria are employed as case studies for the EU's trade relations with West Africa. The study finds that the special and differential treatment provisions in the EU-Ghana EPA text are insufficient to support the economic development of Ghana. Although power asymmetry permeates relations between Nigeria and the EU, it does not necessarily determine that the outcome of these interactions will always favour the EU. It also finds that Nigeria is not as dependent as Ghana on the EU for its trade and investment relations because the former exports oil to the EU tax free. Moreover, Nigeria's trade and economic strategies are to strengthen its bilateral trade and investment relationship with the United Kingdom post-Brexit. The thesis concludes that notwithstanding that the proponents of the EPAs stated that the objective of the EPAs would be to promote free trade and economic development of the ACP countries; the conduct of the EU in the negotiations, the textual interpretation of GATT Article XXIV and the text of the agreements indicate that the EU-ECOWAS EPA is likely to reinforce asymmetry in the trade relationship between it and countries that signed the agreements.